1992 Major Repairs and Modifications to Key Equipment and Installations at Paipote Smelter - Chile - A. Rios (The Minerals, Metals and Materials Society, 1993)
ENAMl's Paipote Smelter commenced operations in 1951. At present, it processes 230,000 tonnes/year of green feed in a conventional smelter, which comprises one reverberatory furnace, two Hoboken, one Peirce-Smith converters and one rotary anode furnace. The feed is composed of 83% copper concentrate and 17% metallic copper precipitates, which results in a feed average grade of 32% of copper content. The final products are 75,000 tonnes/year of copper anodes and 48,000 tonnes/year of sulphuric acid. At present, the plant is undergoing a modernization to expand the smelter capacity to 300,000 tonnes/year of green feed and increase the sulphuric acid production to 100,000 tonnes/year. This will be achieved with the installation of an El Teniente Converter and an expansion in the acid plant. The work began in November 1991 and is scheduled to be in operaton by March 1993. The paper provides an overview of the modernization plans and results achieved to-date.